PENDIDIKAN DEMOKRASI - Ade Wahyudi; Ade Tegar; Arifandi; Budi Pratama; Reza Raihanda; Musdanil; Rizky wanda; Rizky maulana; Satria; Tirta; Yogi; Zikri; Zulkarnain (BULLET : Jurnal Multidisiplin Ilmu, 2022)
Democracy comes from the Greek words "Demos" and "Kratos". Demos means people or audience and Kratos means government. Democracy is a system of government that allows and provides rights, freedoms for its citizens and opinions and participates in decision-making in government. Democracy is carried out so that the needs of the general public can be met. Policy-making in a democracy depends on the wishes and aspirations of the people in general. By determining policies in accordance with the wishes of the people, in a democratic country will create people's satisfaction. A country itself is said to have implemented a democratic system.